Do Agricultural Reforms Increasing the Prosperity of Indonesian Farmers? - Priyagus; ZA, Saida Zainurossalamia; Widayanti, Nurfiza; Darma, Dio Caisar (Jurnal AGRISEP, 2024)
Since several decades, agricultural movements have been supporting the majority of villages in Indonesia. Agricultural reform is a new program organized by the government that started in 2019. In this context, the objectivity of the paper is to examine causality between technology adoption (TA), capital subsidies (CS), educational skills (ES), and health and scholarships (H&S) on farmers' prosperity  (FP). Using a time–series regression simulation, the investigation is focused on agricultural reform in the era of President Jokowi, to be precise in the 2nd period (2019–2023). In Indonesia, there are simultaneous parallel effects of technology adoption, capital subsidies, educational skills, and health and scholarships on the farmers' prosperity. When testing partially, the result is that technology adoption as well as health and scholarships have a positive effect on the farmers' prosperity. Yet, capital subsidies and educational skills actually have a negative effect on the farmers' prosperity. Explicitly, the consistency of agricultural reform is expected to be accessible to all farmers.